2020
DOI: 10.1016/j.jtocrr.2020.100020
|View full text |Cite
|
Sign up to set email alerts
|

Desensitizing Effect of Cancer Cachexia on Immune Checkpoint Inhibitors in Patients With Advanced NSCLC

Abstract: Introduction: Programmed cell death 1 (PD-1) inhibitors have become standard treatment for patients with advanced NSCLC. However, few studies have focused on the impact of cancer cachexia on the efficacy of PD-1 or programmed death-ligand 1 (PD-L1) inhibitors among patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 33 publications
6
44
0
Order By: Relevance
“…There are no data on clinically useful predictors for host antitumor immunity 6,7 . Recently, we proposed a hypothesis regarding the suppressive effects of cancer cachexia on PD‐1/PD‐L1 inhibitors in patients with metastatic non‐small cell lung cancer (NSCLC) 8 . Patients with cachexia exhibited worse overall response rate (ORR) and progression free survival (PFS) values than those without it, even if they were potentially sensitive to anti‐programed cell death 1/programed cell death ligand 1 (PD‐1/PD‐L1) inhibitor and have high PD‐L1 expression in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no data on clinically useful predictors for host antitumor immunity 6,7 . Recently, we proposed a hypothesis regarding the suppressive effects of cancer cachexia on PD‐1/PD‐L1 inhibitors in patients with metastatic non‐small cell lung cancer (NSCLC) 8 . Patients with cachexia exhibited worse overall response rate (ORR) and progression free survival (PFS) values than those without it, even if they were potentially sensitive to anti‐programed cell death 1/programed cell death ligand 1 (PD‐1/PD‐L1) inhibitor and have high PD‐L1 expression in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Recently, we proposed a hypothesis regarding the suppressive effects of cancer cachexia on PD-1/PD-L1 inhibitors in patients with metastatic non-small cell lung cancer (NSCLC). 8 Patients with cachexia exhibited worse overall response rate (ORR) and progression free survival (PFS) values than those without it, even if they were potentially sensitive to anti-programed cell death 1/programed cell death ligand 1 (PD-1/PD-L1) inhibitor and have high PD-L1 expression in cancer cells. Impaired nutritional status 9 potentially attenuated the host antitumor immunity in a preclinical study, and several other studies that measured the bodyweight of patients with NSCLC supported our findings.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have demonstrated that cancer cachexia or sarcopenia adversely affects the clinical outcome of PD-1 or PD-L1 inhibitor monotherapy. [11,12] Meanwhile, no previous studies have evaluated the e cacy of PD-1/PD-L1 inhibitor plus chemotherapy, the current standard primary treatment for advanced NSCLC, separately in the existence of cancer cachexia, as shown in this study. Although cancer cachexia has an adverse impact on clinical outcomes among patients with advanced NSCLC, it has not been incorporated as a stratifying factor in most clinical trials.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, cancer cachexia potentially has a desensitizing effect in patients with high PD-L1 expression who potentially have an increased sensitivity to PD-1 or PD-L1 inhibitors. [12] PD-1/PD-L1 inhibitor plus chemotherapy might not be effective for all patients with advanced NSCLC. [5][6][7] Thus, it is essential to identify populations that do not respond to PD-1/PD-L1 plus chemotherapy to achieve further survival bene ts.…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that cancer cachexia may be a poor prognostic factor for disease control and survival after ICI monotherapy. [16][17][18] However, there are few reports investigating whether cancer cachexia is a prognostic factor for chemoimmunotherapy in patients with NSCLC. This study investigated the impact of cancer cachexia on the therapeutic outcome of combined chemoimmunotherapy in patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%